La influencia de la dimensión de género en el Trabajo Social - Fombuena Valero, Josefa (Cuadernos de Trabajo Social, 2006)
This qualitative research explains the influence of gender on the interventions of female social workers and the difficulties they encounter not only as women who provide care for women, but also as a result of the categories which color the contributions made by participating female practitioners: a fragile professional framework, the existence of isomorphism related to the complaints of female professionals and clients, the subordinated position to which women have been confined in public institutions and the conflict between rights and care.